Togo: Politics, economy and society in 2006 - Dirk Kohnert (Africa Yearbook Volume 3: Politics, Economy and Society South of the Sahara in 2006, 2007)
The political accord between the government and major opposition parties in August 2006 was welcomed internationally as a major breakthrough, in view of the aftermath of rigged presidential elections and subsequent political turmoil in 2005. The formation of a transitional government of national unity under Yawovi Agboyibo, renowned opposition leader, gave rise to optimistic forecasts concerning the preparations for early free and fair parliamentary elections in June 2007, which would be the first after decades of autocratic rule. – – Die politische Einigung zwischen der Regierung und den wichtigsten Oppositionsparteien im August 2006 wurde international als großer Durchbruch begrüßt, angesichts der Folgen der manipulierten Präsidentschaftswahlen und der darauf folgenden politischen Unruhen im Jahr 2005. Die Bildung einer Übergangsregierung der nationalen Einheit unter dem bekannten Oppositionsführer Yawovi Agboyibo gab Anlass zu optimistischen Prognosen hinsichtlich der Vorbereitungen für vorgezogene freie und faire Parlamentswahlen im Juni 2007, die die ersten nach Jahrzehnten autokratischer Herrschaft sein würden.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2006; domestic policy; foreign affairs; socio-economic development; period under review 2006